Macroeconomics determinants of Malaysia housing price index / Siti Hajar Abu Bakar - Abu Bakar, Siti Hajar (Faculty of Business Management, 2017)
This paper indicate about Malaysia has experienced the foremost changes of house price for over the past few years. This study will show that the performances of house prices in Malaysia are generally caused by the macroeconomics factor. One of it is the growth of economic that is gross domestic product rate. The housing price in Malaysia also influenced by household income because it related to the affordability of buyers to own a house. Moreover, there are strong inverse relationship between interest rates and house prices. That is, when the house prices rise and the interest rate drop. The main objective of this study is to measure the connection between macroeconomic variables and the housing price index. The specific objectives show which significant the macroeconomic variables affect the most on house price index. Dependent variable in this research is housing price index while the independent variables of this research will used of household income, interest rate, and GDP rate is obtained from the quarterly time series of year 1997 until 2015. In the process of findings, there are few types of analysis were tested by using Eview Version 7, there are Pearson correlation coefficient, multiple regression analysis, multicollinearity statistics. This study shows a house that has dual roles which are as a consumption and investment tools also. Thus, this paper is useful for speculators, investors and buyers to know which factors to account for in housing investment decision. This paper can serve as a guide and initiative for the government in stabilizing the residential housing price in Malaysia